Hubungan Penggunaan Gadget dengan Kejadian Insomnia Pada Siswa Siswi Kelas X SMA Negeri 9 Kota Tangerang Selatan - Lela Kania Rahsa Puji; Sigit Probowani (Edu Masda Journal, 2019)
One of the causes of insomnia in adolescents is most often caused by habit factors such as adolescent lifestyles who are hungry for technology especially use of gadgets. This study aims to determine the relationship of use of gadgets with the incidence of insomnia in adolescents class X in SMA Negeri 9 Tangerang Selatan. This study used correlation study with cross sectional time approach. Research respondents are 103 respondents of all students of grade X SMA Negeri 9 Kota Tangerang Selatan using proportional stratified random sampling technique. The intensity of gadget usage was measured by the reliability value questionnaire of 0.862 and insomnia was measured by the reliability value questionnaire of 0.769. Data analysis using Chi Square . Result of data analysis with Chi Square  with p value of 0.000 (p <0,05), showed that there was no correlation between intensity of use of gadgets with insomnia in adolescent in SMA Negeri 9 Kota Tangerang Selatan.